(untitled) (Bangladesh Rice Journal, 2021)
Declination of available water resources is threatening the dry season crop production in Bangladesh. Sustainable water management is crucial need to meet future food production. This study was aimed to determine futuristic water management strategy for rice cultivation. Both surface and groundwater is getting scarce in north-west region, whereas abundant of fresh surface water creating opportunities to irrigate dry season crops in south-central region. This study has outlined irrigation management for rice cultivation and groundwater utilization in water scarce area of north-west region. More than 75% of annual rainfall occurred during monsoon and crops other than monsoon often faced water shortage. Timely establishment of T. Aus rice on 01 May accounted average 183 mm supplemental irrigation for north-west and south-west region. Transplanting of T. Aman rice before 24 July found the low risk period of drought and gave about 1 t ha-1 yield advantage than late transplanting after 15 October. Supplemental irrigation in drought year gave up to 26% yield advantage than the rain-fed condition of T. Aman rice in experimental plot. Over exploitation of groundwater by famers for crop cultivation makes the groundwater status worsen. Farmers used 38% excess water than the actual requirement for Boro rice cultivation. For that annual groundwater withdrawal was higher than annual recharge causing groundwater level depletion in most of the districts. Groundwater table went below suction limit of shallow tubewell (STW) during dry season and thus it become unable to operate. Improved distribution system with plastic pipe, buried pipe could save about 25% of irrigation water. Alternate wetting and drying (AWD) irrigation method saved 20-25% water than farmer’s practice. Application of these on-farm water management technologies in Boro rice reduced water demand and made the groundwater balance positive as well as reduced the groundwater withdrawal pressure. On the contrary, irrigation with less saline surface water resources in river and canals of south central regions could expand Boro production and increased land productivity. Intervention of low lift pump with plastic pipe distribution in non-saline tidal areas could increase land productivity. Besides, trapped freshwater in to the canals inside the polders and re-excavation of these canals would make crop intensification. Thus, additional food production could help to achieve sustainable development goal and sustained food security. Bangladesh Rice J. 25 (1) : 37-50, 2021